2015
DOI: 10.3727/096368914x685230
|View full text |Cite
|
Sign up to set email alerts
|

Human Amnion-Derived Stem Cells Have Immunosuppressive Properties on NK Cells and Monocytes

Abstract: Human amnion-derived cells are considered to be a promising alternative cell source for their potential clinical use in tissue engineering and regenerative medicine because of their proliferation and differentiation ability. The cells can easily be obtained from human amnion, offering a potential source without medical intervention. It has been proven that human amnion-derived cells express immunosuppressive factors CD59 and HLA-G, implying that they may have an immunosuppressive function. To assess the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…Although it has previously been reported that hAMTCs act directly on monocytes (Magatti et al , ) and that amniotic‐derived cells decrease the production of TNF α and IL‐6 cytokines in LPS‐stimulated monocytes (Li et al , ), we here provided the first evidence that hAMTCs and their CM induce macrophage differentiation in the promonocytic U937 cell line or peripheral blood monocytes, in the absence of any other exogenous agents. Importantly, we demonstrated that hAMTCs or their CM favour the generation of macrophages with M2‐like features, even in a M1‐conditioned environment, consequently affecting their functions, such as higher phagocytosis.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Although it has previously been reported that hAMTCs act directly on monocytes (Magatti et al , ) and that amniotic‐derived cells decrease the production of TNF α and IL‐6 cytokines in LPS‐stimulated monocytes (Li et al , ), we here provided the first evidence that hAMTCs and their CM induce macrophage differentiation in the promonocytic U937 cell line or peripheral blood monocytes, in the absence of any other exogenous agents. Importantly, we demonstrated that hAMTCs or their CM favour the generation of macrophages with M2‐like features, even in a M1‐conditioned environment, consequently affecting their functions, such as higher phagocytosis.…”
Section: Discussionmentioning
confidence: 43%
“…We found that CM obtained from hAMSC culture affects both central and effector memory T lymphocyte subsets, significantly reduces the expression of markers associated with Th1 and Th17 populations and significantly induces the regulatory T cells compartment (Pianta et al , ). Furthermore, not only T lymphocytes but also the in vitro proliferation of B cells (Li et al , ), the cytotoxicity of natural killer cells (Li et al , ) and the migration of neutrophils and macrophages (Li et al , ; Tan et al , ) have been shown to be affected by amniotic cells and their CM. Moreover, we and others have demonstrated that amniotic cells and their CM impair the development of dendritic cells from primary monocytes (Magatti et al , ; Kronsteiner et al , ; Banas et al , ; Magatti et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated that both hAECs and AMSC express IL‐4, IL‐6, IL‐8, HLA‐G and TGF‐β. IL‐10 and cyclooxygenase expressions were upregulated upon IL‐1β stimulation or co‐culturing with NK cells . These data indicate that hAEC‐derived cytokines also modulate NK cell activity.…”
Section: Immunomodulatory Properties Of Amniotic Epithelial Cellsmentioning
confidence: 74%
“…In line with a rapid transition from the inflammatory to the reparative phase (Manuelpillai et al, ) was the evidence of the increased local expression of M2Mφ‐associated genes and the lower IL12b:IL10 ratio recorded in the presence of hAECs. This suggested an Mφ skewing towards M2 phenotype, along with simultaneous higher expression of IL10, essential to prevent the production of proinflammatory cells or factors (Li et al, ). The cytokine expression profile is specular in CTR: Here, the prevalence of proinflammatory M1Mφ markers (CD68) and the local presence of ongoing inflammatory molecules (high concentration of IL12b mRNA) persisted over 28 days probably leading to a spontaneous fibrotic scar evolution.…”
Section: Discussionmentioning
confidence: 99%